2021
DOI: 10.1371/journal.pone.0247395
|View full text |Cite
|
Sign up to set email alerts
|

Motor strategy during postural control is not muscle fatigue joint-dependent, but muscle fatigue increases postural asymmetry

Abstract: The aim of this study was to investigate the effects of ankle and hip muscle fatigue on motor adjustments (experiment 1) and symmetry (experiment 2) of postural control during a quiet standing task. Twenty-three young adults performed a bipedal postural task on separate force platforms, before and after a bilateral ankle and hip muscle fatigue protocol (randomized). Ankle and hip muscles were fatigued separately using a standing calf raise protocol (ankle fatigue) on a step and flexion and extension of the hip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 60 publications
2
14
0
Order By: Relevance
“…Nonetheless, our results are in line with previous research, which reported fatigue-related impairments for balance performance and, thus, postural control resulting in significant increases in postural sway ( Sadowska and Krzepota, 2016 ; Penedo et al, 2021 ), sway velocity ( Zech et al, 2012 ), sway area ( Bedo et al, 2020 ; Moon et al, 2020 ; Penedo et al, 2021 ), as well as decreases of the stability index ( Cooper et al, 2020 ) during stable and unstable bipedal and unipedal stance in healthy young adults. For instance, Zech et al (2012) investigated the effects of a localized fatigue versus a general fatigue protocol on static and dynamic balance in male handball athletes.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Nonetheless, our results are in line with previous research, which reported fatigue-related impairments for balance performance and, thus, postural control resulting in significant increases in postural sway ( Sadowska and Krzepota, 2016 ; Penedo et al, 2021 ), sway velocity ( Zech et al, 2012 ), sway area ( Bedo et al, 2020 ; Moon et al, 2020 ; Penedo et al, 2021 ), as well as decreases of the stability index ( Cooper et al, 2020 ) during stable and unstable bipedal and unipedal stance in healthy young adults. For instance, Zech et al (2012) investigated the effects of a localized fatigue versus a general fatigue protocol on static and dynamic balance in male handball athletes.…”
Section: Discussionsupporting
confidence: 93%
“…Accordingly, they assumed that there might exist different sensorimotor control mechanisms within the postural control system responsible for static and dynamic balance which are affected differently by the applied fatigue protocols. Moreover, Penedo et al (2021) examined the effects of local PF on postural sway and lower limb muscle activation in healthy young adults. While postural sway increased, no changes in muscle activation were observed after PF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a fatigue-induced shift of the mean ML COP position to the right was found during the QS-EO task in the present study (shift to a more positive value indicating a shift to the right; Fig 2B ), possibly suggesting a fatigue-induced asymmetry of posture. This would be consistent with the results of a recent study showing an increased asymmetry index between preferred and non-preferred legs (based on muscle activation during quiet standing) with ankle and hip muscle fatigue, possibly indicating a shift in the control of posture towards the preferred leg [ 42 ]. This suggests that the contribution of a more reliable leg to control posture could increase with fatigue.…”
Section: Discussionsupporting
confidence: 92%
“…This definition is used to describe a temporary decline in the ability to perform physical activities [ 63 , 64 ]. As reported in the literature, muscle fatigue reduces postural stability, regardless of the tired muscle area, and the asymmetry of the load on the lower limbs increases [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%